Penerapan SMOTE dalam Pemodelan CHAID pada Data Keberhasilan Mahasiswa PPKU IPB - Ririn Fara Afriani; Mohammad Masjkur; Utami Dyah Syafitri (Xplore: Journal of Statistics, 2019)
Bogor Agricultural University (IPB) as the third rank of Indonesian non polytechnic universities in 2017 requires new students to join the General Competency Education Program (PPKU) for two semesters to improve the quality of human resources. Student achievement success can be determine from the student's academic status, where the student's academic status is divided into two, which are Drop Out (DO) and not DO. Only 1% of PPKU students who are drop out.. This means there is a data imbalance. One of the method used to handled that is Synthetic Minority Oversampling Technique (SMOTE) method. Classification analysis used is the Chi-Square Automatic Interaction Detection (CHAID) method to identify the factors that influence the success of PPKU students. The application of SMOTE to the 2016/2017 PPKU student data was able to improve the ability of classiï¬cation trees with the average values â€‹â€‹of accuracy, sensitivity, and specificity to 0.718, 0.575, and 0.72. The factors that influence the success of IPB's PPKU students are the entry point, gender, and regional origin.